Management Control System Package And Entrepreneurial Competency Influence On Business Performance With The Moderating Role Of Business Strategy - Bustanul Arifin; Mulyanah Mulyanah; Febiola Martina (Review of Accounting and Taxation, 2022)
Purpose - This study aims to determine the influence of the Management Control System Package’s elements on Entrepreneurial Competency; and Entrepreneurial Competency on SMEs Business Performance. Design/methodology/approach - This research uses quantitative research. Sampling methods in this research using purposive sampling technique, This research used Partial Least Square as data analysis technique. Finding - The result showed that the elements of Cultural Control; Planning Control; Cybernetic Control; Rewards and Compensation Control has influence on Entrepreneurial Competency’s improvement, meanwhile Administration Control has no influence on Entrepreneurial Competency’s. Then, Entrepreneurial Competency has influence on Business Performance. However, Business Strategies has no influence to moderate the relationship between Entrepreneurial Competency on Business Performance of SMEs in Serang city. Originality - This is the first study that discusses the implementation of the MCS Package in Serang City SMEs.